Obesity and cardiometabolic risk factors: from childhood to adulthood - Drozdz, Dorota; Alvarez-Pitti, Julio; Wójcik, Małgorzata; Borghi, Claudio; Gabbianelli, Rosita; Mazur, Artur; Herceg-Čavrak, Vesna; Lopez-Valcarcel, Beatriz Gonzalez; Brzeziński, Michał; Lurbe, Empar; Wühl, Elke (Nutrients, 2021)
Obesity has become a major epidemic in the 21st century. It increases the risk of dyslipidemia, hypertension, and type 2 diabetes, which are known cardiometabolic risk factors and components of the metabolic syndrome. Although overt cardiovascular (CV) diseases such as stroke or myocardial infarction are the domain of adulthood, it is evident that the CV continuum begins very early in life. Recognition of risk factors and early stages of CV damage, at a time when these processes are still reversible, and the development of prevention strategies are major pillars in reducing CV morbidity and mortality in the general population. In this review, we will discuss the role of well-known but also novel risk factors linking obesity and increased CV risk from prenatal age to adulthood, including the role of perinatal factors, diet, nutrigenomics, and nutri-epigenetics, hyperuricemia, dyslipidemia, hypertension, and cardiorespiratory fitness. The importance of ‘tracking’ of these risk factors on adult CV health is highlighted and the economic impact of childhood obesity as well as preventive strategies are discussed.
Gesehen am 20.01.2022